THE MARKETING EFFECTIVENESS IN START-UP BUSINESS: A SYSTEMATIC LITERATURE REVIEW FROM 1973-2023 - Hodijah, Cucu; Hendrayani, Eka; Tarigan , Miska; Suprianto, Ghalib; Suryathi, Wayan (Jurnal Riset Bisnis dan Manajemen, 2024)
In today's rapidly evolving business environment, understanding dynamic marketing effectiveness is essential for startups. This study explores how flexible marketing strategies can adapt to technological advancements, shifting consumer behaviors, and global market changes. A systematic literature review of 740 scholarly articles identified 35 relevant studies. These articles address various facets of marketing effectiveness, including technology integration, strategic learning, social media use, and internationalization. The findings provide startups with practical guidance on enhancing marketing effectiveness by adopting innovative technologies and aligning with market trends. This study serves as a valuable resource for entrepreneurs and marketers, offering actionable insights into successful marketing strategies in a dynamic business landscape.